Learning to forecast, risk aversion, and microstructural aspects of financial stability - Alessio Emanuele Biondo (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
This paper presents a simulative model of a financial market, based on a fully operating order book with limit and market orders. The heterogeneity of traders is characterized not only with regards to their trading rules, but also by introducing a behavioral individual risk aversion and a learning ability influencing the process of expectations formation. Results show that individual learning may play a role in stabilizing the aggregate market dynamics, whereas the risk aversion has, counterintuitively, the opposite effect.
Keywords: E44; E47; C63; 330; order book; learning to forecast; risk aversion; agent-based models